The Corporate Sustainability Reporting Directive: Preliminary Conclusions from the First Reports - Karolina SZKUDLAREK (Communications of International Proceedings, 2025)
Nowadays, companies cannot operate ignoring the external environment. Some companies publish reports on social responsibility and sustainable development. So far, these reports have not had a defined scope, which has hindered their comparability. Starting with the 2024 reports, some companies will have to report the above information following European Sustainability Reporting Standards, which may improve the situation in this area. The purpose of this article is to examine the first reports prepared in accordance with the ESRS. The study involved an analysis of the sustainability reports of companies listed on the Warsaw Stock Exchange (included in the WIG20 index as of August 14, 2025). The findings indicate that the standards introduced have not resolved previously identified issues, including the limited comparability of reports and the challenges associated with verifying their reliability.
Keywords: sustainability reporting; corporate social responsibility; CSRD; ESRS